2018
DOI: 10.1186/s12934-018-1008-6
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Gα-cAMP/PKA signaling pathway in cellulose utilization of Chaetomium globosum

Abstract: BackgroundThe canonical heterotrimeric G protein-cAMP/PKA pathway regulates numerous cellular processes in filamentous fungi. Chaetomium globosum, a saprophytic fungus, is known for producing many secondary metabolites, including cytotoxic chaetoglobosin A (ChA), as well as abundant cellulase and xylanase.ResultsHere we report on the functional characterization of this signaling pathway in C. globosum. We blocked the pathway by knocking down the putative Gα-encoding gene gna1 (in the pG14 mutant). This led to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 46 publications
1
7
0
1
Order By: Relevance
“…The PKA pathway, which plays an antagonistic role in the regulation of CAZymes compared with AMPK pathway, is also involved in the CCR. G protein-coupled receptors, the cellular second messenger cAMP, and adenylate cyclase are all involved in the PKA pathway and affected the downstream targets by phosphorylation cascades (Nogueira et al, 2015;Yang et al, 2018). PKA is essential for CCR as its deletion leads to a misfunction of CCR with impaired nucleus location effect of repressors and partial derepression of CAZymes, which is consistent with the result obtained by the PkaA deletion strain with a varied degree of derepression of cellulase genes under different culture conditions (Kunitake et al, 2019).…”
Section: Signal Pathway In Filamentous Fungisupporting
confidence: 79%
“…The PKA pathway, which plays an antagonistic role in the regulation of CAZymes compared with AMPK pathway, is also involved in the CCR. G protein-coupled receptors, the cellular second messenger cAMP, and adenylate cyclase are all involved in the PKA pathway and affected the downstream targets by phosphorylation cascades (Nogueira et al, 2015;Yang et al, 2018). PKA is essential for CCR as its deletion leads to a misfunction of CCR with impaired nucleus location effect of repressors and partial derepression of CAZymes, which is consistent with the result obtained by the PkaA deletion strain with a varied degree of derepression of cellulase genes under different culture conditions (Kunitake et al, 2019).…”
Section: Signal Pathway In Filamentous Fungisupporting
confidence: 79%
“…Additionally, CreA is differentially phosphorylated depending on the presence of PkaA, resulting in altered characteristics for import in the nucleus [25]. A positive role of the cAMP pathway as well as the heterotrimeric G-protein pathway on cellulase gene expression and secondary metabolism was further shown in Chaetomium globosum [26, 27]. Besides functions in development, a role of the cAMP pathway in secondary metabolism was shown for Aspergillus fumigatus , Pestalotiopsis microspora and Fusarium graminearum [2830].…”
Section: Introductionmentioning
confidence: 99%
“…In cAMP signalling pathway, PKA activity is essential for regulation of primary and secondary metabolism [ 35 , 36 ]. Our data showed that knockout of mrPDE could induce PKA kinase activity (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The cyclic adenosine monophosphate (cAMP) is a second messenger in eukaryotic and prokaryotic cells [ 16 ]. cAMP was produced by adenylyl cyclase (AC) with ATP as substrate [ 17 ].…”
Section: Introductionmentioning
confidence: 99%